Outcomes after curatively intended treatment of limited peritoneal metastases and thermal ablation for liver metastases from colorectal cancer - Balachandran Rogini; Sørensen Mette Møller; Funder Jonas Amstrup; Knudsen Anders Riegels; Iversen Lene Hjerrild (Pleura and Peritoneum, 2023)
Peritoneal metastases (PM) and liver metastases (LM) are present simultaneously in up to 2 % of patients at the time of their colorectal cancer (CRC) diagnosis. Curatively intended treatment includes cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) combined with LM resection. A less invasive treatment for LM is ablation. We aimed to estimate overall survival (OS), disease-free survival (DFS) and postoperative data in patients managed simultaneously with CRS, HIPEC and radiofrequency ablation (RFA) as first choice.